Temporal Trends of Kidney Failure in Basrah Governorate: A Study in Medical Geography - Tawffiq Abdul Karim Al-Hajjaj , Researcher .Ali; Salih Abood Al-Kaabi, Prof. Dr. Amal (Basra studies journal, 2025)
The present study aims to uncover the temporal trends (annual and monthly) of kidney failure in Basrah Governorate based on statistical analyses of relevant data. The study reached several findings concerning these trends. It was found that there is an upward trend in the disease, with variations in recorded cases and deaths during the period 2013–2023. This increase is attributed to population growth and the rise in chronic diseases such as diabetes, hypertension, and heart disease, which constitute the main causes of kidney failure. Pollution was also identified as a contributing factor. Regarding monthly trends, it was observed that the number of cases increases in January, while deaths peak in both January and July.